Translating cutting-edge neuroscience to rehabilitation practice in concussion management: 11 things the rehabilitation clinician should know about the pathophysiology of sports-related concussion - Chen, Y.; Herrold, A. A.; Gallagher, V. T.; Reilly, J. L.; Parrish, T.; Breiter, H. C. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Mild traumatic brain injury or concussion is a common sports injury. Concussion involves physical injury to brain tissue, and vascular and axonal damage that manifest as transient and often nonspecific clinical symptoms. Concussion diagnosis is challenging and the relationship between brain injury and clinical symptoms is unclear. The purpose of this commentary is to translate cutting-edge neuroscience to rehabilitation practice. We (1) highlight potential biomarkers that may improve our understanding of concussion and its recovery, (2) explain why researchers must address the paucity of concussion research in female athletes, and (3) present female-specific factors that should be accounted for in future studies. Integrating objective, quantitative measures of concussion pathophysiology with concussion history, genetics and genomics will help caregivers identify concussed athletes, tailor recovery protocols and protect athletes from potential long-term effects of cumulative head impact.